1994
DOI: 10.1126/science.7973727
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the p53-Regulated Protein Gadd45 with Proliferating Cell Nuclear Antigen

Abstract: GADD45 is a ubiquitously expressed mammalian gene that is induced by DNA damage and certain other stresses. Like another p53-regulated gene, p21WAF1/CIP1, whose product binds to cyclin-dependent kinases (Cdk's) and proliferating cell nuclear antigen (PCNA), GADD45 has been associated with growth suppression. Gadd45 was found to bind to PCNA, a normal component of Cdk complexes and a protein involved in DNA replication and repair. Gadd45 stimulated DNA excision repair in vitro and inhibited entry of cells into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
561
3
6

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 893 publications
(590 citation statements)
references
References 23 publications
18
561
3
6
Order By: Relevance
“…Recent research suggests that p53 may participate in the repair machinery (Smith et al, 1994;Wang et al, 1995a;Ford and Hanawalt, 1995;. For example (Wang et al, , 1995a, it was shown that p53 binds to and modulates the repair activity of the nucleotide excision repair factors XPB and XPD.…”
Section: Other Biochemical Activities Of P53mentioning
confidence: 99%
“…Recent research suggests that p53 may participate in the repair machinery (Smith et al, 1994;Wang et al, 1995a;Ford and Hanawalt, 1995;. For example (Wang et al, , 1995a, it was shown that p53 binds to and modulates the repair activity of the nucleotide excision repair factors XPB and XPD.…”
Section: Other Biochemical Activities Of P53mentioning
confidence: 99%
“…Although all of the reports suggest that global NER activity is decreased in cells which lack WTp53 protein function, these same studies also reported either decreased or no change in clonogenic UV-radiation survival (Ishizaki et al, 1994;DeFrank et al, 1996;Smith et al, 1995) or increased UV-radiation survival (Afzal et al, 1994;Fan et al, 1994;Sands et al, 1994;Ford and Hanawalt, 1995;McKay et al, 1997). It would therefore seem that the WTp53 protein's role in DNA repair may be pleiotropic, depending on the nature of DNA damage (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the targets of p53, Gadd45 and p21, are known to interact with PCNA (Smith et al, 1994;Waga et al, 1994), but the significance of the Gadd45/PCNA interaction is not at all clear (Kearsey et al, 1995). p21 cannot be the mediator of the p53-dependent focus formation of PCNA and the subsequent S-phase DNA damage checkpoint because these can occur in cells deficient in p21 as shown by the data of Figure 1a and Figure 3c.…”
Section: Discussionmentioning
confidence: 99%